(untitled) (Applied Biological Research, 2023)
This study was aimed to develop a milk-based date beverage (MDB) that combined the nutrient properties of milk with dates (Phoenix dactylifera L.). Since the addition of dates to milk resulted in the curdling of milk, therefore various types and levels of stabilizing salts were screened. Amongst the different stabilizing salt evaluated, trisodium citrate @ 0.15% (w/w of milk) was found most suitable. Different levels of date extract and sugar, prepared in milk (3.0% fat and 8.5% MSNF), were used to optimize the most acceptable DMB as per response surface methodology using two factor central composite rotatable design comprising of 13 experiments. The levels of date extract and sugar ranged from 13 to 17 and 3 to 7% (w/w of milk), respectively. The suggested solution from RSM analysis for DMB was the date extract level of 15.0% and sugar level of 5.6%. The developed product had 21.65% total solids, 2.70% fat, 3.08% protein, 15.08% carbohydrates and 0.79% ash. The study revealed that an acceptable quality of DMB can be manufactured by the addition of date.